Biophysical needs and perceptions on senior day care of the functional elderly in the village of Dayap in Calauan, Laguna, Philippines - Torres, R. V. (2003)
The Senior Day Care is necessary to satisfy the biopsychosocial need of the functional elderly. The study aimed to determine the unmet biopsychosocial needs and perceptions on senior day care of 100 functional elderly, aged 60 years and above, in the village of Dayap in Calauan, Laguna. Majority of the respondents, with ages ranging from 60 to 89, were married and earning for their living. The respondents' level of of awareness on Senior Day Care was low at 32% but their willingness to participate was high at 71% after the concept was explained. Major reasons for their willingness to join were their desire to be productive, active, healthy and strong. Identified reasons for taking part in the Senior Day Care were lack of time and preference to stay at home. The cultural acceptable senior day care services needed were medical screening, nutritional counselling, livelihood, health education, and physical fitness. Psychological counselling socialization, and recreational arts and crafts were the least preferred services.
Keywords: Calauan (Laguna); Day care